2018
DOI: 10.1002/ijc.31774
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes play roles in sequential processes of tumor metastasis

Abstract: Overwhelming evidence demonstrates that exosomes, a series of biologically functional small vesicles of endocytic origin carrying a variety of active constituents, especially tumor-derived exosomes, contribute to tumor progression and metastasis. This review focuses on the specific multifaceted roles of exosomes in affecting sequenced four crucial processes of metastasis, through which cancer cells spread from primary to secondary organs and finally form macroscopic metastatic lesions. First, exosomes modulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
116
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 108 publications
(202 reference statements)
0
116
0
Order By: Relevance
“…These reports, together with the present results, suggest that EVs may play a relevant role in the transmission of deleterious effects from peripheral blood to brain in different pathological situations, including hyperammonemia and MHE. There is overwhelming evidence that exosomes, a subtype of EVs, contribute to tumor progression and metastasis [49,50], to the immunopathology in infectious diseases [51] and to neurodegenerative diseases [52]. We show here that EVs also contribute to the induction of neuroinflammation and motor incoordination in hyperammonemia and likely MHE, in which motor incoordination is induced by similar mechanisms.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…These reports, together with the present results, suggest that EVs may play a relevant role in the transmission of deleterious effects from peripheral blood to brain in different pathological situations, including hyperammonemia and MHE. There is overwhelming evidence that exosomes, a subtype of EVs, contribute to tumor progression and metastasis [49,50], to the immunopathology in infectious diseases [51] and to neurodegenerative diseases [52]. We show here that EVs also contribute to the induction of neuroinflammation and motor incoordination in hyperammonemia and likely MHE, in which motor incoordination is induced by similar mechanisms.…”
Section: Discussionmentioning
confidence: 49%
“…Peripheral EVs may also trigger neuroinflammation. Li et al [49] purified serum EVs from a mice model of endotoxemia with LPS and injected them to normal mice. They found that this induced microglial activation, astrogliosis, and increased expression of pro-inflammatory IL-6 and TNFα in hippocampus and cerebral cortex in recipient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recent works have shown the pre-metastatic niche in ovarian cancer to be a prevalent precondition of metastasis [5]. The pre-metastatic niche is a preformed microenvironment made possible by exosomes secreted by the primary tumor site prior to widespread metastasis [6][7][8]. These exosomes optimize the environment for ovarian cancer colonization, outgrowth, and metastasis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular membrane trafficking via exosomes and other plasma membrane-derived vesicles can promote tumor growth and metastasis [50]. Many studies have demonstrated that CD133-containing vesicles are involved in a series of important biological processes such as cell differentiation, cancer progression, and extracellular cell communication [15][16][17].…”
Section: Discussionmentioning
confidence: 99%